Teknologi Peningkatan Kualitas Hasil Panen Jagung (Zea mays L.) Di Lahan Berpasir: Technology for Improving Corn Crop Quality (Zea mays L.) In Sandy Land - Saijo Saijo (J-Plantasimbiosa, 2022)
The aim of the study was to evaluate the yield quality of maize (Zea mays L.) cultivated on sandy soil. It was carried out at the Research Garden of the Faculty of Agriculture and Forestry and the Laboratory of the Faculty of Agriculture and Forestry, University of Muhammadiyah Palangkaraya for 4 months starting from August-November 2021. The results of the research on the vegetative phase in the form of plant height, number of leaves, and stem diameter had a significant effect. The results of the observation of the generative phase, both dry weight of cobs without cob, dry weight of seeds given treatment have a very significant effect on crop yields. The best maize yields were using a combination of dolomite lime treatment at a dose of 6 t ha-1 and cow manure at a dose of 30 t ha-1 which resulted in a dry weight of cobs weighing 246.2 g cob-1 and dry shelled weight weighing 190.0 g per 100 seeds.